Nursing management of facial neuritis in a patient with multiple myeloma during the interval between chemotherapy (1例多发性骨髓瘤患者化疗间歇期合并面神经炎的护理) - ZHAO Jing (赵晶); LI Hui (李辉) (中西医结合护理)
This paper summarize the nursing practice of facial neuritis in a patient with multiple myeloma during the interval between chemotherapy. In addition to facial care, rehabilitation training and emotion care, Traditional Chinese Medicine characteristic nursing techniques such as acupoint application and acupuncture were carried out to relieve the symptoms of facial paralysis and anxiety of the patient, and ensure the following chemotherapy. (本文总结1例多发性骨髓瘤患者化疗间歇期合并急性面神经炎的护理经验。在面部护理、康复训练、情志护理的基础上, 采用穴位贴敷、针灸疗法等中医特色护理措施, 有效改善患者面瘫症状, 缓解焦虑情绪, 确保后续化疗疗程的顺利进行。)